A REVIEW OF MEDICAL TOURISM AND HOW IS IT APPLICABLE TO THE ISLAND OF FIJI - Veitogavi, Kitione; Nosa, Vili (Advances in Social Sciences Research Journal, 2021)
The purpose of this study is to undertake a literature review on the theme of medical tourism. We will use Fiji as a case study. The paper uses a systemic review of secondary data with a comprehensive data extraction methodology to match the subject areas with the specific countries being investigated. This literature review used 61 articles. Most medical tourism cases are driven by a desire for more economical healthcare services than those in most medical tourists’ home nations. In order to drive essential improvements, the quality of services encourages investment in technology and facilities in medical tourism-active countries. With increased medical tourism investment and patient numbers, Asian Pacific countries have gained substantial foreign revenue. There are also many questions and uncertainties, despite the many positive aspects of medical tourism, such as the lack of a database to store patient records anywhere in the world or on the ground, growing medical tourism difficulties for local health services, and social and political factors such as corruption, political wars, and government uncertainty, all of which can have a significant impact on a country’s medical care. Fiji has begun efforts to develop its medical tourism sector, setting up Oceania Hospital, and investing in Ba and Lautoka hospitals, operated and equipped by the Health Care Fiji brand. However, Fiji requires extensive government support, skilled and qualified personnel, valuable partnerships in its local sector, and infrastructural upgrades to incorporate medical tourism fully.